Response of water to electric fields at temperatures below the glass transition: A molecular dynamics analysis - Hu, Xiaohu; Elghobashi-Meinhardt, Nadia; Gembris, Daniel; Smith, Jeremy C. (The journal of chemical physics, 2011)
The electric field dependence of the structure and dynamics of water at 77 K, i.e., below the glass transition temperature (136 K), is investigated using molecular dynamics simulations. Transitions are found at two critical field strengths, denoted - E - 1 - E1 - and - E - 2 - E2 - . The transition around - E - 1 - ≈3.5 - E1≈3.5 - V/nm is characterized by the onset of significant structural disorder, a rapid increase in the orientational polarization, and a maximum in the dynamical fluctuations. At - E - 2 - ≈40 - E2≈40 - V/nm, the system crystallizes in discrete steps into a body-centered-cubic unit cell that minimizes the potential energy by simultaneous superpolarization of the water molecular dipoles and maximization of the intermolecular hydrogen bonds. The stepwise and discontinuous increase of the orientational polarization with the increasing electric field indicates that the dipole relaxation in the electric field is highly cooperative.
Gesehen am 30.06.2022